Mauritania - The Rainfed Natural Resource Management Project - Ba, Amadou Omar (2012)
This article, extracted from an Implementation Completion Report, centers on the Mauritania Natural Resources Management Project ( Projet de Gestion des Ressources Naturelles en Zones Pluviales - PGRNP ) ( 1998-2003 ), which had two specific objectives : 1) empowering rural communities, i.e., providing skills to organize and manage common resources, and obtain access to financing; and (2) improving the institutional environment in the rural sector, including securing access to natural resources. Lessons learned from this project including the need for a critical mass of investment activities in communities and adequate time to build community capacity; transparent, well-publicized procedures to neutralize political interference and cornering by the elite; baseline data and a functional monitoring and evaluation system; decentralized project management; and using mass media communications.